Biomechanics-mediated endocytosis in atherosclerosis - Wang, Jinxuan; Xu, Jianxiong; Liu, Tianhu; Yu, Chaoping; Xu, Fengcheng; Wang, Guixue; Li, Shun; Dai, Xiaozhen (Frontiers in Cardiovascular Medicine, 2024)
Biomechanical forces, including vascular shear stress, cyclic stretching, and extracellular matrix stiffness, which influence mechanosensitive channels in the plasma membrane, determine cell function in atherosclerosis. Being highly associated with the formation of atherosclerotic plaques, endocytosis is the key point in molecule and macromolecule trafficking, which plays an important role in lipid transportation. The process of endocytosis relies on the mobility and tension of the plasma membrane, which is sensitive to biomechanical forces. Several studies have advanced the signal transduction between endocytosis and biomechanics to elaborate the developmental role of atherosclerosis. Meanwhile, increased plaque growth also results in changes in the structure, composition and morphology of the coronary artery that contribute to the alteration of arterial biomechanics. These cross-links of biomechanics and endocytosis in atherosclerotic plaques play an important role in cell function, such as cell phenotype switching, foam cell formation, and lipoprotein transportation. We propose that biomechanical force activates the endocytosis of vascular cells and plays an important role in the development of atherosclerosis.